Hierarchical cluster analysis of three-dimensional reconstructions of unbiased sampled microglia shows not continuous morphological changes from stage 1 to 2 after multiple dengue infections in Callithrix penicillata - Daniel Guerreiro Diniz; Daniel Guerreiro Diniz; Geane Oliveira Silva; Thais Barroso Naves; Taiany Nogueira Fernandes; Sanderson Corrêa Araújo; José Antonio Picanço Diniz; Luis Henrique Seabra de Farias; Marcia Consentino Kronka Sosthenes; Cristovam Guerreiro Diniz; Daniel Clive Anthony; Pedro Fernando da Costa Vasconcelos; et al. (Frontiers Media S.A., 2016)
It is known that microglial morphology and function are related, but few studies have explored the subtleties of microglial morphological changes in response to specific pathogens. In the present report we quantitated microglia morphological changes in a monkey model of dengue disease with virus CNS invasion. To mimic multiple infections that usually occur in endemic areas, where higher dengue infection incidence and abundant mosquito vectors carrying different serotypes coexist, subjects received once a week subcutaneous injections of DENV3 (genotype III)-infected culture supernatant followed 24 hours later by an injection of anti-DENV2 antibody. Control animals received either weekly anti-DENV2 antibodies, or no injections. Brain sections were immunolabeled for DENV3 antigens and IBA-1. Random and systematic microglial samples were taken from the polymorphic layer of dentate gyrus for 3-D reconstructions, where we found intense immunostaining for TNFα and DENV3 virus antigens. We submitted all bi- or multimodal morphological parameters of microglia to hierarchical cluster analysis and found two major morphological phenotypes designated types I and II. Compared to type I (stage 1), type II microglia were more complex; displaying higher number of nodes, processes and trees and larger surface area and volumes (stage 2). Type II microglia were found only in infected monkeys, whereas type I microglia was found in both control and infected subjects. Hierarchical cluster analysis of morphological parameters of 3-D reconstructions of random and systematic selected samples in control and ADE dengue infected monkeys suggests that microglia morphological changes from stage 1 to stage 2 may not be continuous.